Centralization of the Educational Field in Applied Linguistics - Megherbi Kder (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
In this linguistic description, we attempt to examine the structure of the educational-learning process as a communicative act in which all of its constituent parts interact, including